DENTAL AMALGAM: EFFECTS OF ALLOY/MERCURY MIXING RATIO, USES AND WASTE MANAGEMENT - Kefi, Kefi I; Maria, Maria A; Majid, Majid Z; Sana, Sana J; Afreen, Afreen M; Fareed, Fareed M; Feroze, Feroze A; Sajid, Sajid H; Adel, Adel S; Iftikhar, Iftikhar A; et al. (Journal of Ayub Medical College Abbottabad, 2011)
Background: Silver dental amalgam is one of the oldest filling materials used in dentistry. The American Dental Association (ADA) has estimated that billions of amalgam restorations have been placed in patients in the last 150 years. Due to the presence of mercury and mishandling during the filling make it more controversial. The objective of this study was to conduct a survey of the use of different brands and to assess any deviations in practice from the hand mixing manual method of elemental mercury and alloy in a pestle/mortar and encapsulated form. Methods: A questionnaire was sent to 250 of randomly selected dental practitioner in various localities of Karachi. Data was analysed to record the specified brands used along with their powder/liquid (P/L) ratio and the different methods for disposing off mercury in this study. Results: The most commonly used form of dispensing method was hand mixing (57%) and only 30% of the dentists followed the manufacturer instruction for hand mixing ratio. Eighty-seven percent of dental amalgam restoration was performed and 13% removed by the dentist per month and the method of disposing the amalgam wastage that 55%, 25%, and 20% dentists were used the sink, bin and other methods respectively in their dental clinics. Conclusion: Amalgam restoration is still popular filling material in the posterior region of the mouth but we need to create awareness among the dentists who do not follow the ADA specifications. Keywords: Dental amalgam, alloy mercury ratio, amalgam wastage, amalgam dispensing